Nationwide emergency department visits for pediatric traumatic spinal cord injury in the United States, 2016–2020 - Crispo, James A. G.; Liu, Lisa J. W.; Noonan, Vanessa K.; Thorogood, Nancy P.; Kwon, Brian K.; Dvorak, Marcel F.; Thibault, Dylan; Willis, Allison W.; Cragg, Jacquelyn J. (Frontiers in Neurology, 2023)
Traumatic spinal cord injury (tSCI) is a debilitating neurological condition resulting in lifelong disability for many individuals. The primary objectives of our study were to describe national trends in incident emergency department (ED) visits for tSCI among children (less than 21 years) in the United States, and to determine the proportion of visits that resulted in immediate hospitalization each year, including stratified by age and sex. Secondary objectives were to examine associations between select characteristics and hospitalization following tSCI, as well as to assess sports-related tSCIs over time, including by individual sport and geographic region. We used the Healthcare Cost and Utilization Project Nationwide Emergency Department Sample to identify ED visits among children between January 2016 and December 2020 for incident tSCI. Diagnosis codes were used to identify tSCI and sports-related injury etiologies. Census Bureau data were used to approximate annual rates of pediatric ED visits for tSCI per 100,000 children. Unconditional logistic regression modeling assessed whether select factors were associated with hospital admission. We found that the annual ED visit rate for tSCI remained relatively stable between 2016 and 2020, with approximately 2,200 new all-cause pediatric ED visits for tSCI annually. Roughly 70% of ED visits for tSCI resulted in hospitalization; most ED visits for tSCI were by older children (15-20 years) and males, who were also more often admitted to the hospital. Notable secondary findings included: (a) compared with older children (15-20 years), younger children (10-14 years) were less likely to be hospitalized immediately following an ED visit for tSCI; (b) patient sex and race were not associated with hospital admission; and (c) American tackle football was the leading cause of sports-related ED visits for tSCI among children. Our findings also suggest that the proportion of sports-related tSCI ED visits may have increased in recent years. Future research should further examine trends in the underlying etiologies of pediatric tSCI, while assessing the effectiveness of new and existing interventions aimed at tSCI prevention.